Survival and factors associated with survival with extracorporeal life support during cardiac arrest: a systematic review and meta-analysis. (2nd May 2022) - Panagides, V; Laine, M; Fond, G; Lebreton, G; Paganelli, F; Michelet, P; Roch, A; Boyer, L; Bonello, L
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Survival after sudden cardiac arrest (CA) remains low at approximately 10% despite recent advances in cardiopulmonary resuscitation (CPR). Extracorporeal life support (ECLS) may be useful to improve outcomes. However, it is resource intensive and associated with significant complications. We therefore performed a meta-analysis of all available observational studies of patients receiving ECLS-facilitated CPR to estimate the overall survival rate to discharge and predictors of survival. Methods: We conducted a literature search in MEDLINE, PubMed EMBASE and the Cochrane Library from inception to September 2020. Studies were included if they focused on ECLS during CPR for CA in adult patients and provided survival data. Results: Among the 1745 articles identified by our search, 81 studies involving 9256 patients were included in the analysis. Overall, the pooled estimated survival was 26.2% at discharge and 20.4% with a good neurological outcome. The heterogeneity across studies was significant for both outcomes. Meta-regressions found a significant association between survival at discharge and lower lactate values (b=-0.1, 95% CI [-0.2; -0.05], p=0.002), intrahospital CA (b= 0.005, 95% CI [0.002; 0.008], p= 0.002), and lower CPR duration (b=-0.009, 95% CI [-0.02; -0.002], p=0.02). After adjustment for age, intrahospital CA, and mean CPR duration, an initial shockable rhythm was the only independent factor associated with survival to discharge (b=0.02, 95% CI [0.007; 0.02], p=0.0004). Conclusion: The overall survival rate on discharge of ECLS-facilitated CPR for CA was 26.2%, and the survival with good neurological outcome was 20.4%. An initial shockable rhythm was the only independent predictor of survival to discharge.